Penerapan Metode Literasi dalam Pembelajaran Bahasa Indonesia di SMA Negeri Restorasi Doreng - Yeremias Bardi; Anastasia Evarista Theresia Astita Bura; Maria Cetrih Angelsa Nati; Weronika Kartika Weka; Sulaiman Sulaiman; Yohanes Swasti Sue (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Indonesian is the national language used as the main means of communication in everyday life, both in education, government, and in the mass media. In this context, literacy methods are important to be applied in the process of learning Indonesian. Indonesian language education at the Senior High School (SMA) level plays an important role in shaping students' literacy skills, both in reading, writing, speaking, and listening. One of the main objectives of learning Indonesian is to develop effective communication skills and improve literacy skills that can support students' academic success and daily lives. The application of appropriate literacy methods is very necessary to help improve the quality of Indonesian language learning. Literacy methods in learning Indonesian can encourage students to be more active in reading, writing, and thinking critically. With the right method, students not only master Indonesian language material, but are also able to apply literacy skills in various life contexts. This study aims to apply literacy methods in learning Indonesian at SMA Negeri Restorasi Doreng. Literacy as the ability to understand, criticize, and produce texts has an important role in improving students' competence in language. The methods applied in this study involve various literacy techniques, such as critical reading, creative writing, and text-based discussions. This research was conducted with a qualitative approach through observation, interviews, and document analysis. The results of the study indicate that the application of literacy methods can improve students' understanding of Indonesian language materials, enrich vocabulary, and hone their writing and speaking skills. In addition, the application of this method also succeeded in building more active student involvement in the learning process. Thus, the literacy method can be used as an alternative to improve the quality of Indonesian language learning at the high school level.